2015
DOI: 10.3892/or.2015.4340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HPV-16 infection on hypopharyngeal squamous cell carcinoma and FaDu cells

Abstract: Hypopharyngeal squamous cell carcinoma is a common type of malignant tumor among head and neck squamous cell carcinomas (HNSCCs). Heavy smoking and/or drinking is associated with the development of HNSCC. However, HNSCC also occurs in individuals that do not drink or smoke, possibly due to infection with the human papilloma virus (HPV). HPV-16 has been shown to be closely associated with the occurrence of several types of cancers. However, its role in hypopharyngeal squamous cell carcinoma remains unclear. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…miR-490-5p expression was also detected in NP69, HaCaT, BICR 18, FaDu, HNE-3 and Detroit 562 cells, and the result demonstrated that miR-490-5p expression in pharyngolaryngeal cancer cells was decreased, particularly in BICR 18 and FaDu cells, which further confirmed that the expression of miR-490-5p was downregulated in pharyngolaryngeal cancer cells. In addition, laryngeal carcinoma is one of the most common head and neck neoplasms, which is mainly represented by squamous cell carcinoma was predominant, BICR 18 and FaDu cells are squamous cells (20,21). Therefore, BICR 18 and FaDu cells were selected for later experiments.…”
Section: Discussionmentioning
confidence: 99%
“…miR-490-5p expression was also detected in NP69, HaCaT, BICR 18, FaDu, HNE-3 and Detroit 562 cells, and the result demonstrated that miR-490-5p expression in pharyngolaryngeal cancer cells was decreased, particularly in BICR 18 and FaDu cells, which further confirmed that the expression of miR-490-5p was downregulated in pharyngolaryngeal cancer cells. In addition, laryngeal carcinoma is one of the most common head and neck neoplasms, which is mainly represented by squamous cell carcinoma was predominant, BICR 18 and FaDu cells are squamous cells (20,21). Therefore, BICR 18 and FaDu cells were selected for later experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several cellular miRNAs are differentially expressed in HPV-positive HNSCC cell lines and in HPV-negative HNSCC cell lines (27). In our previous study (24), we detected the expression of miR-15a in HNSCC tissues, and found that miR-15a expression was significantly higher in HPV-positive than in HPV-negative HNSCC. These results suggested that miR-15a plays an important role in HPV-positive HNSCC and acts as an anti-oncogene.…”
Section: Discussionmentioning
confidence: 81%
“…Our previous study (24) showed that miR-15a is highly expressed in HPV-positive tissues and cells. It may be speculated that HPV-positive tumors have a better prognosis.…”
Section: Introductionmentioning
confidence: 98%
“…Wang found miR‐203 could inhibit tumour growth and metastasis through PDPN . MiR‐15a was up‐regulated in HPV‐positive HSCC and might induce tumour apoptosis via BCL2L2 and BCL2 …”
Section: Discussionmentioning
confidence: 99%
“…23 MiR-15a was up-regulated in HPV-positive HSCC and might induce tumour apoptosis via BCL2L2 and BCL2. 24,25 However, many miRNAs are oncogenic by targeting tumour suppressor genes. miR-21 was widely accepted as 'oncomiR', which was overexpressed in various types of cancers including lymphoma, oesophageal cancer, LSCC, HSCC and SCC of oral cavity.…”
Section: Discussionmentioning
confidence: 99%